Hadith on Avoiding Boredom in Learning from The Perspective of Educational Psychology - Dwi Yanti, Nurul Azizah; Hartati, Hartati; Muthi'ah, Anisatun (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Hadith is the second source of Islamic knowledge after the Quran. This means that hadith covers all aspects of activities that can be used as a reference, including education and the sciences that it encompasses. The problem in the world of education today is that teachers and students are forced to use a limited range of learning methods. This condition is caused by the lack of activities and creativity that educators and students engage in during the learning process. This situation has occurred during the time of the Prophet Muhammad, and hadiths related to avoiding boredom in learning have emerged. From this issue, research objectives were established. The purpose of this research is to determine the quality, quantity, and meaning of hadiths related to avoiding boredom in learning from the perspective of educational psychology that is adjusted to teaching strategies. The method used in this study is literature review (pentakhrijan hadith). The results of the study indicate that (1) the hadith